2021
DOI: 10.1111/1365-2745.13808
|View full text |Cite
|
Sign up to set email alerts
|

Selection on convergent functional traits drives compositional divergence in early succession of a tallgrass prairie restoration experiment

Abstract: 1. Plant biodiversity is often partitioned into taxonomic diversity (species composition and abundance), phylogenetic diversity (breadth of evolutionary lineages)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 119 publications
(147 reference statements)
0
12
0
Order By: Relevance
“…Both PD and MNTD are strong measures of habitat filtering, which are relevant to our study on changes in metrics over time, and with communities planted as seeds and as plugs (Miller et al 2017). In preliminary analyses, MPD (another commonly used phylogenetic metric in community ecological studies) did not covary with PD in our experiment whereas PD and MNTD did correlate strongly and significantly (Hipp et al 2018; Karimi et al 2021). We do not report results from MPD in the main text, but they can be found in Figure S1.…”
Section: Methodsmentioning
confidence: 56%
See 2 more Smart Citations
“…Both PD and MNTD are strong measures of habitat filtering, which are relevant to our study on changes in metrics over time, and with communities planted as seeds and as plugs (Miller et al 2017). In preliminary analyses, MPD (another commonly used phylogenetic metric in community ecological studies) did not covary with PD in our experiment whereas PD and MNTD did correlate strongly and significantly (Hipp et al 2018; Karimi et al 2021). We do not report results from MPD in the main text, but they can be found in Figure S1.…”
Section: Methodsmentioning
confidence: 56%
“…If, as some studies have shown, PD and FD are important predictors of ecosystem function, then sites that maintain higher levels of these forms of diversity may preserve ecosystem function even in the face of decreased species richness (Zirbel et al 2017; Barber et al 2019). Furthermore, restored communities with higher initial FD and PD may also be more “adaptable” to specific restoration conditions, or to future changes (Karimi et al 2021). Our work supports planting high diversity mixes to obtain high diversity plant communities, if diversity is a desired restoration outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence indicates current restoration practices result in lower phylogenetic diversity than untilled, native remnants, and are not functionally equivalent (Barak et al, 2017 ). Including phylogenetic diversity in management and restoration practices could promote system resiliency and lead to higher success rates of restoration and management (Barber et al, 2019 ; Hipp et al, 2015 ; Karimi et al, 2021 ), an especially important consideration in the face of an ongoing extinction event and changing climate.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates current restoration practices result in lower phylogenetic diversity than untilled, native remnants, and are not functionally equivalent (Barak et al, 2017). Including phylogenetic diversity in management and restoration practices could promote system resiliency and lead to higher success rates of restoration and management (Barber et al, 2019;Hipp et al, 2015;Karimi et al, 2021), an especially important consideration in the face of an ongoing extinction event and changing climate. A sampling at one time of the growing season has the potential to influence observed phylogenetic diversity by under-sampling taxonomic diversity (Jantzen et al, 2019;Park et al, 2018) due to temporal phenological niche separation and phenological conservatism (i.e., flowering time) (Kochmer & Handel, 1986;Wright & Calderon, 1995).…”
Section: Discussionmentioning
confidence: 99%